2021
DOI: 10.3390/vaccines9111259
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Perception toward COVID-19 Vaccines among Adults in Jazan Province, Saudi Arabia

Abstract: Background: Saudi Arabia is one of the countries that initiated early vaccination programs despite the global challenges concerning the availability of COVID-19 vaccines. Massive vaccination campaigns have been undertaken in the country; however, negative perception and hesitancy toward vaccines may exist which could reduce public response to vaccination. Further, studies evaluating the current perception and attitude toward COVID-19 vaccines are scarce. Thus, this study aims to assess the community attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
17
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
6
17
2
Order By: Relevance
“…A prior study revealed that approximately two-thirds of the respondents had positive perceptions of the presently available COVID-19 vaccines given in Saudi Arabia [30]. Similarly, in our cohort, a total of 62.7% of the respondents had a positive perception regarding COVID-19 vaccination in the survey, where everyone was vaccinated.…”
Section: Discussionsupporting
confidence: 73%
“…A prior study revealed that approximately two-thirds of the respondents had positive perceptions of the presently available COVID-19 vaccines given in Saudi Arabia [30]. Similarly, in our cohort, a total of 62.7% of the respondents had a positive perception regarding COVID-19 vaccination in the survey, where everyone was vaccinated.…”
Section: Discussionsupporting
confidence: 73%
“…Aging was proposed as a factor contributing to prevent vaccines among BPH patients according to our study. This is identical to the previous survey conducted in Saudi Arabia that the elderly was less willing to be vaccinated (43.85% vs 67%) (25,30). A possible reason might be the age restriction for newly established SARS-CoV-2 vaccine programs at the initial stage.…”
Section: Discussionsupporting
confidence: 83%
“…23,[55][56][57] However, this is not universal. [58][59][60] Consequently, our aim was to evaluate the acceptance of the COVID-19 vaccination and the related factors among university students in UAE. We chose university students for this initial study as a number of these people will become influential in the future.…”
Section: Introductionmentioning
confidence: 99%